Syumuliyah of Islam: A Framework for Achieving SDG 3 (Good Health and Well-being) - Jakiyudin, Ahmad Havid; Hardianti, Hardianti (Universitas Muhammadiyah Magelang, 2024)
The 2030 Sustainable Development Goals (SDGs), particularly Goal 3: Good Health and Well-being, emphasize the importance of healthy living and well-being for all. This study explores the Islamic concept of Syumuliyah – the holistic and comprehensive nature of Islamic teachings – as a potential framework for achieving this critical SDG. Through a qualitative library research approach, this study examines how Islamic principles, including those related to health, hygiene, and spiritual well-being, can contribute to the realization of SDG 3. Findings indicate that Islamic teachings offer a comprehensive approach to health, encompassing physical, mental, and spiritual dimensions. Key elements include the importance of cleanliness, proper nutrition, physical activity, and spiritual practices such as prayer and reflection. Notably, medical education can be traced back to the verses of the Qur'an and the Sunnah of the Prophet Muhammad (SAW), emphasizing the importance of preventive healthcare and holistic well-being. By embracing the Syumuliyah of Islam, individuals and communities can cultivate healthier lifestyles and contribute to the overall well-being of society, thereby advancing the objectives of SDG 3.